The idealised image of the Australian home: A myth in the making - Low, Irene Oi Ling (Curtin University, 2015)
As set against the prevailing social, cultural and architectural concept of the idealised house and sense of home, this thesis argues that there are inherent specific signifying mechanisms of the media which attempt to universalise and naturalise meanings and values for what the home represents. By adopting the theoretical strategy of Roland Barthes’ Mythologies and employing a semiotic approach, this thesis challenges the idealised image of the Australian home in the context of architecture and media advertising.